1999
DOI: 10.1111/1475-4983.00100
|View full text |Cite
|
Sign up to set email alerts
|

The first thecideide brachiopod from the Jurassic of North America

Abstract: ABSTRACT. Restudy of a hardground fauna from the Middle Jurassic of south-western Utah revealed the presence of thecideoid brachiopods. The absence of separated dorsal valves and the effects of abrasion and diagenesis hampered the description of the specimens. However, serial sectioning of complete shells revealed a thecidellinid which in its morphology and shell microstructure resembled Rioultina Pajaud from the Middle Jurassic of Europe. Important morphological differences clearly separate the new specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
1
13
0
1
Order By: Relevance
“…The few specimens that are available (Pl. 1, figs 1–5) confirm the earlier discoveries (Nekvasilová 1967; Baker 1989 a ; Baker and Wilson 1999) that initially the ventral interarea is very small and narrow, little more than a strip of shell material on either side of a relatively large externally undemarcated (Pl. 1, figs 4, 5) pseudodeltidium.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…The few specimens that are available (Pl. 1, figs 1–5) confirm the earlier discoveries (Nekvasilová 1967; Baker 1989 a ; Baker and Wilson 1999) that initially the ventral interarea is very small and narrow, little more than a strip of shell material on either side of a relatively large externally undemarcated (Pl. 1, figs 4, 5) pseudodeltidium.…”
supporting
confidence: 85%
“…In specimens where the valves are conjoined (Pl. 1, figs 1–3; see also Baker and Wilson 1999, pl. 1, fig.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The morphology of Enallothecidea is considered (Baker and Carlson 2010, p. 659) to be close to the ancestral morphotype. Research by Baker and Wilson (1999) on their new genus Stentorina indicated that the early juvenile ventral umbo was palintropic. Therefore, the palintrope and the delthyrium may be regarded as plesiomorphic characters in thecideides.…”
Section: Resultsmentioning
confidence: 99%